PERANCANGAN SISTEM PEMBAYARAN (BILLING SYSTEM) PASIEN DI RUMAH SAKIT UMUM INANTA PADANGSIDIMPUAN - ayu lestary; Ria Masniari Lubis; arnita . (Kebijakan, Promosi Kesehatan dan Biostatiskik, 2015)
ABSTRACT Still today Inanta General Hospital using manually billing system serviced on collecting, gathering, and calculating patient bills that considered less effective caused longer time services and quite a lot of human resources. By using computerized billing system, the obstacles either direct or indirect such as mistakes in calculating hospital fee, lost data transaction, error documentation and slow transaction handling will be quickly and appropriately assisted thus it can improve the quality of administrative service in hospital. The study aims to plan billing system in the Inanta General Hospital using computer technology MYSQL and C#. The development of this system is designed by using the System Life Development Cycle (SLDC) method consists of three stages, namely analysis, design, and implementation. The result of this system programming consist which includes the input design namely patient identity, doctors data, drug data, and medical records. The file design is a storage and database processing. The output design created consist of two reports, namely the report outpatient care cost and inpatient care cost. Billing system program will give the easiness in administrative health service. It is expected that the hospital will apply this program in the administrative hospital.